Single Amino Acid Repeats Connect Viruses to Neurodegeneration - Lucchese, Guglielmo; Kanduc, Darja (Current Drug Discovery Technologies, 2014)
We report on a high level of octapeptide matching between HCV, HIV-2, MPV, MUV, EBV, HHV-6, and CMV, and human brain antigens that, when altered, have been specifically associated with neuropathologies such as amyotrophic lateral sclerosis, spinocerebellar ataxia, frontotemporal degeneration, Huntington disease, Parkinson disease, cognitive impairment, aphasia and oculomotor apraxia. Quantitatively, the extent of the viral octapeptide sharing with neurodegeneration- associated proteins is in excess when analyzed in a stochastic expectation context. Qualitatively, two main features characterize the peptide matching: 1) many common sequences are single amino acid repeats, and 2) mostly, the shared octapeptides are part of experimentally validated epitopes, thus suggesting an immune crossreactive potential of the viral peptides shared with brain antigens involved in neurodegeneration. The present study may have relevance for peptidebased therapeutic approaches to block potential autoimmune crossreactions in neurological diseases and dysfunctional behavior.
Keywords: immune crossreactivity